Qur’an Learning Management Based on The Qur’ani Sidogiri Method: Effective and Efficient Strategies for Children of Early Age - Fakhriyah, Durratul; Rosi, Fathor (Mudir : Jurnal Manajemen Pendidikan, 2025)
This study aims to describe and analyze the management of Qur'anic learning based on the Sidogiri Qur'anic Method (MQS) at TPQ Al Mubarak, Tenggir Barat, Situbondo, as an effective and efficient strategy in early childhood education. The research method used is descriptive qualitative, with data collection techniques including in-depth interviews, participatory observation, and documentation. The results show that the learning management at TPQ Al Mubarak includes flexible planning tailored to students' abilities, implementation that combines classical and individual methods (talaqqi and tasmi’), and daily evaluations based on observation and discussions among educators. The successful implementation of MQS is supported by certified teacher training, regular coaching, parental involvement, and the integration of Tauhid values. MQS not only improves technical skills in reading the Qur'an but also shapes Qur'anic character in early childhood. This study recommends MQS as an alternative learning model that can be widely adapted by TPQs in regions with similar conditions.